ANALISIS PENANGANAN SAMPAH BERBASIS MASYARAKAT DI DESA DOPLANG, KECAMATAN TERAS, KABUPATEN BOYOLALI - Puspitasari, Lifia; Warsono, Hardi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2020)
Abstract Doplang village is included as one of the areas in Boyolali which is identified as slums and the criteria for waste management are considered inadequate. The implementation of waste management in Doplang Village is done by involving participation of the community, but it’s still not optimal. CBSWM implementation is seen through legal, institutional, operational technical, financial, and community participation aspects. The purpose of this study is to describe and analyze the implementation of CBSWM in Doplang Village and identify the constraints on CBSWM in Doplang Village. In public management it’s necessary to manage external relations. The research method used is descriptive qualitative. The results showed that the CBSWM in Doplang Village was carried out with a persuasive approach by the KSM Kampung Asri as a waste management party in Doplang 3R TPST. Constraints experienced are include lack of operational costs, understanding of environmental cleanliness isn’t yet good, the lack of coordination between TPST 3R Doplang managers with parties from the TPA and related agencies. Suggestions that can be given are expansion of CBSWM area coverage by KSM Kampung Asri, as well as the need for technical assistance in developing CBSWM activities in Doplang Village and budgeting priorities by related agencies.